A new approach for determining the thickness of material plate using gamma backscattering method. (July 2020) - Chuong, Huynh Dinh; Ngoc Trang, Le Thi; Tam, Hoang Duc; Nguyen, Vo Hoang; Thanh, Tran Thien
Abstract: This study proposes a new approach to determine the thickness of the material plate. This approach uses Monte Carlo simulation to construct the calibration curve of the ratio R versus the thickness of the material plate (R is the ratio of area under a scattering peak for a given thickness to that for a saturation thickness). Using this calibration curve, the unknown thickness of a material plate is determined by experimentally measuring the ratio R. To validate the proposed approach, we performed 39 measurements for 13 aluminum samples with thicknesses in the range of 7.00 mm–35.20 mm. The results showed that except for two measurements with relative deviations of 5.45% and 6.17%, the relative deviation for the remaining measurements is less than 5%. Besides, the method for estimating the maximum measurable thickness with the desired deviation was presented, which shows good agreement between theoretical calculation and experimental value. The obtained results are the basis for completing the thickness measurement system using semi-empirical methods in further studies. Highlights: A new approach for determining thickness of material plate based on gamma scattering method. The calibration curve for determining thickness is constructed based on Monte Carlo simulation. The measurement uses a low activity source with a simple experimental arrangement. The method for determining the MMT of gamma scattering technique is first presented.